2014
DOI: 10.1007/s12053-014-9271-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence consumers’ acceptance of future energy systems: the effects of adjustment type, production level, and price

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 38 publications
0
35
0
3
Order By: Relevance
“…In essence, such settings remove the need for people to think about adjustments, making sustainability the "default" setting. Although these "green defaults" have tremendous potential for reducing energy consumption, it is also important to respond to consumers' desire to be, or at least to feel, in control of the devices in their homes by permitting adjustments and opt-outs [6,11]. We argue that perception is what matters here, as people may not repeatedly adjust settings once they are comfortable.…”
Section: Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, such settings remove the need for people to think about adjustments, making sustainability the "default" setting. Although these "green defaults" have tremendous potential for reducing energy consumption, it is also important to respond to consumers' desire to be, or at least to feel, in control of the devices in their homes by permitting adjustments and opt-outs [6,11]. We argue that perception is what matters here, as people may not repeatedly adjust settings once they are comfortable.…”
Section: Contributionsmentioning
confidence: 99%
“…Research on smart homes and smart energy systems has found that consumers prioritize autonomy even more than convenience: they prefer the ability to manually adjust smart energy technologies versus allowing them to operate without human intervention [3,4,6]. Because convenience is often seen an important added value of smart home technologies, this is an important finding.…”
Section: Perceived Controlmentioning
confidence: 99%
“…Moral considerations affect policy support: acceptability of energy policies is higher when people are highly aware of energy problems and feel morally obliged to reduce these problems . Furthermore, energy policies and energy system changes are evaluated as more acceptable when they do not seriously threaten people's freedom of choice Steg et al, 2006;Schuitema et al, 2010;Leijten et al, 2014). More generally, people evaluate energy policies and changes in energy systems as more acceptable when these policies and changes are expected to have more positive and less negative individual and/or collective consequences (Dietz et al, 2007;Shwom et al, 2010;see Schuitema and Jakobsson Bergstad, 2012, for a review).…”
Section: Acceptability Of Energy Policies and Changes In Energy Systemsmentioning
confidence: 99%
“…On the one hand, according to the ISTAT (Italian National Institute of Statistics) [9], the age groups more willing to an active participation in public and/or social issues are [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], and 45-54 years old, with an education level equal or higher than a high school diploma, and without a significant difference between males and females. The next step was to investigate, within these "boundaries", people's behaviours and needs on both gamification and co-design issues.…”
Section: A Survey On Gamification and Co-design Issues: The Followedmentioning
confidence: 99%
“…Finally, in line with the Theory of Planned Behavior [34], studies suggest that energy technology acceptance is partially explained by perceived control over the technology [35]. Direct control DR programs may achieve reliable reductions, but participation rates are estimated at 10 % [8].…”
Section: Behavioral Science Foundationsmentioning
confidence: 99%